When citizens complain of dissatisfaction with public services performance in Bahrain - Busenan, Dr. Ebrahim Farhan Mubarak (The journal of contemporary issues in business and government, 2022)
Public sector contributes a significant proportion to the GDP in most of the world economies. Public sector of Bahrain plays an effective role in the delivery of basic services that serve the country and all members of society. Complaints are an important way for the public sector organizations to be accountable to the public. In addition, to providing a valuable prompts to review organizational performance and the conduct of people that work within and for it. This policy focused on citizens‟ complaints and how its effects on the public services performance, as well as to highlight the importance of complaints as a tool to improving the public services performance in the public sector organizations of Bahrain. The scope of this policy is public sector services organizations of Bahrain. 6 questions were used for the variable of public services performance, one of them covering the complaints, (Expectations complaints from citizens about performance of public services delivery taken seriously. The main findings of this policy is to focus on complaints that present from citizens about performance of public services as an important tool to public sector of Bahrain in order to the implementation and development solutions to improve and enhance performance of public services. Moreover, practical implications, when citizens complain they want their concerns to be taken seriously and, it is necessary, matters put right. This can increase the possibility of restoring satisfaction and trust of citizens in public services performance.